Dutch oral health care quality measures: a modified Delphi study. (14th April 2020) - Righolt, Amy J.; Duijster, Denise; van der Wees, Philip J.; Listl, Stefan; Smits, Kirsten P. J.
Abstract : Objectives: Quality measures offer opportunities for evaluation and improvement of the quality of oral health care. This study describes the development of a core set of oral health care quality measures for adults in the Netherlands, which can be used in dental practice. Materials and methods: A comprehensive two‐stage approach was used, consisting of: (1) identification of an initial set of measures based on appraised literature; and (2) a four‐round modified RAND/UCLA Appropriateness Method to establish measures that are relevant, appropriate and important to oral health care. Measures were rated anonymously on a nine‐point Likert scale, ranging from 1 (lowest rating) to 9 (highest rating), followed by a group discussion to reach consensus. Multiple key stakeholder groups in the Dutch oral health care field were involved in the Delphi rounds, including dental professionals, scientists and representatives from Dutch oral health care organisations. Results: The study resulted in a core set of 13 oral health care quality measures. The measures cover domains related to oral disease outcomes, oral treatment and preventive services, patient experiences, patient safety, and organisational aspects of oral health care. In addition, the study led to the identification of 49 structural aspects of oral health care that are important to measure. Discussion: To our knowledge, this is the first study combining appraised literature from a systematic review and a rigorous multi‐stage procedure with extensive stakeholder involvement to develop a core set of oral health care quality measures. In the next phase, the measures will be tested on feasibility, reliability, and will be piloted and implemented in practice.